Rural-urban differences in children's dietary diversity in Ethiopia: A Poisson decomposition analysis - Hirvonen, Kalle (International Food Policy Research Institute, 2016)
An emerging body of literature shows how low diversity in diets is associated with increased risk of chronic undernutrition and micro-nutrient deficiencies in young children. The latest available Demographic and Health Survey data for Ethiopia reveals unusually large differences in children's dietary diversity between rural and urban areas. Applying recently developed non-linear decomposition methods, this large rural-urban gap in dietary diversity can almost entirely be explained by differences in household wealth, parental education, and access to health services between rural and urban areas.